2013
DOI: 10.5392/jkca.2013.13.11.1046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Fidelity Simulation-Based Training of Nursing Students according to their Learning Styles

Abstract: The purpose of this study was to establish basic materials for providing a learning type specific simulation education through identifying the differences in self-efficacy, problem solving ability and clinical competence before and after a learning type specific simulation education, with 145 3rd-year nursing students at a university as the study subjects. This study is a single-group, before-and-after designed experiment for verifying the learning type specific effects after simulation education. As a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This is consistent with the results of the study conducted by Kim (2012) [5], where the team-based simulation learning group showed significant improvements in clinical competence compared to the case-based learning and nursing skills training group. Further, the results support previous findings that simulation-based education enhances nursing students' clinical competence [25].…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the results of the study conducted by Kim (2012) [5], where the team-based simulation learning group showed significant improvements in clinical competence compared to the case-based learning and nursing skills training group. Further, the results support previous findings that simulation-based education enhances nursing students' clinical competence [25].…”
Section: Discussionsupporting
confidence: 89%
“…Based on such results, it would be eventually necessary to promote the production of nurses fully equipped with adaptability to clinical settings by actively inducing students' voluntary participation through simulation education, giving positive feedbacks on it, and improving the learning satisfaction/attitude based on interest in learning and voluntary motivation through debates of various clinical cases. The mean score of self-efficacy was 3.50 out of 5.00, which was higher than 2.94 of the research by Kim & Park (2013). In the research by Kim & Park(2013), it was measured when the semester began before applying the simulation program to subjects.…”
Section: Discussionmentioning
confidence: 64%
“…The mean score of self-efficacy was 3.50 out of 5.00, which was higher than 2.94 of the research by Kim & Park (2013). In the research by Kim & Park(2013), it was measured when the semester began before applying the simulation program to subjects. In this study, it was measured after learning all the basic nursing skills in the basic nursing practice class.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, two studies showed that simulation education programs on basic and advanced cardiac life support and resuscitation effectively increased the knowledge of medical staff about treatments and equipment and boosted their confidence in emergency situations (Flisher, ; Hoadley, ). Moreover, Kim and Pak () showed recently that a simulation education program improved the self‐efficacy of nurses; specifically, it improved their confidence towards their ability to acquire theoretical and practical knowledge.…”
Section: Introductionmentioning
confidence: 99%